Local activation of α2 adrenergic receptors is required for vagus nerve stimulation induced motor cortical plasticity - Ching-Tzu Tseng (Nature Portfolio, 2021)
Abstract Vagus nerve stimulation (VNS) paired with rehabilitation training is emerging as a potential treatment for improving recovery of motor function following stroke. In rats, VNS paired with skilled forelimb training results in significant reorganization of the somatotopic cortical motor map; however, the mechanisms underlying this form of VNS-dependent plasticity remain unclear. Recent studies have shown that VNS-driven cortical plasticity is dependent on noradrenergic innervation of the neocortex. In the central nervous system, noradrenergic α2 receptors (α2-ARs) are widely expressed in the motor cortex and have been critically implicated in synaptic communication and plasticity. In current study, we examined whether activation of cortical α2-ARs is necessary for VNS-driven motor cortical reorganization to occur. Consistent with previous studies, we found that VNS paired with motor training enlarges the map representation of task-relevant musculature in the motor cortex. Infusion of α2-AR antagonists into M1 blocked VNS-driven motor map reorganization from occurring. Our results suggest that local α2-AR activation is required for VNS-induced cortical reorganization to occur, providing insight into the mechanisms that may underlie the neuroplastic effects of VNS therapy.